Intention to Read to Newborns Following a Brief Reading Promotion Intervention among Low-Income Pregnant Women - Clay, Deshanett; Ahlers-Schmidt, Carolyn R.; Benton, Mary; Engel, Matt; Brown, Molly (Kansas Journal of Medicine, 2019)
Introduction. Reading to children can increase word knowledge and success in school. The American Academy of Pediatrics recommends beginning reading at birth. However, children from low-income families are exposed to less words, including reading exposure, than children from high-income families. Methods.xPregnant women attending a community prenatal education program targeted at high-risk and low-income populations were recruited into this study. Participants completed a pre-survey, engaged with a brief educational intervention, then completed a matched post-survey. Surveys assessed perceived benefits, intended behaviors, and self-efficacy regarding reading to their child. Results. Of 61 eligible participants, 54 (89%) completed the study. Participants reported being Black (33%), White (30%), Hispanic (28%), and other race (9%). Average gestational age at enrollment was 27 weeks (range 13 to 38 weeks). The average age of respondents was 26 years (SD = 7.2); 46% reported being pregnant for the first time. Following the intervention, no change in knowledge regarding benefits of reading was observed, however, baseline knowledge was high (58% - 94%). At post-test, significantly more women reported it was important to start reading to their child at birth (83% vs 56%; p < 0.001) and that they planned to start reading to their child at birth (70% vs 50%; p = 0.001). Conclusions. A brief educational intervention showed promise in increasing pregnant women’s intentions to read to their children and should be considered in conjunction with other reading promotion programs. Follow-up to assess actual reading behavior is needed. Kans J Med 2019;12(2):50-52.